Investigation of Anti-diabetic potential of the Flowers of Hibiscus syriacus L. Plant (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present study was carried out to identify the phytochemicals and evaluate the anti-diabetic activity of Hibiscus syriacus L. Ethanol and aqueous extracts were studied for the Oral Glucose Tolerance Test (OGTT) study and sub-acute effects on alloxan-induced diabetic rats. Blood glucose levels, serum lipid profiles and histopathological study of the pancreas were performed. Alloxan induced diabetes in rats by damaging the beta cells of the pancreas. After H. syriacus L. treatment blood glucose, TC, TG, LDL and VLDL of all tested rats were significantly decreased and at the same time HDL was increased in alloxan-induced diabetic rats. However, the ethanolic extract of H. syriacus showed more significant anti-diabetic activity than the aqueous extract. The results reveal that H. syriacus L. flowers extract may have potent anti-diabetic activity, justifying the use of the drug for the treatment of diabetes mellitus.